Communities and law : politics and cultures of legal identities - Barzilai, Gad. (Ann Arbor : University of Michigan Press, 2003)
Offers an alternative approach to liberalism and to communitarianism, with an empirical focus on Israel.
Legal cultures, communities, and democratic political cultures -- State legal culture: domination, identities, and the politics of rights -- The Arab-Palestinian community in a Jewish (and democratic) state -- Feminism, community, and law -- Religious fundamentalism and law: the Jewish ultra-Orthodox (Haredi) community and legal culture -- Conclusions: the return to the communal space.
Includes bibliographical references (pages 313-343) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Law -- Social aspects -- Israel; Minorities -- Legal status, laws, etc. -- Israel; Droit -- Aspect social -- Israël.; Minorités -- Droit -- Israël.; LAW -- Jurisprudence; LAW -- General Practice; LAW -- Reference; LAW -- Essays; LAW -- Paralegals & Paralegalism; LAW -- Practical Guides; POLITICAL SCIENCE -- Civics & Citizenship; Law -- Social aspects; Minorities -- Legal status, laws, etc; Israel; Minderheden; Recht; Cultuur